DNA Barcoding of Selected Zombie-Ant Fungi in Hutan Simpan Labis, Johor - Ak Kendawang, Kenneth Yohansen; Jeremiah Sia Yiao Rong,; Yap Jing Wei, (Enhanced Knowledge in Sciences and Technology, 2024)
Ophiocordyceps sp., or as known as zombie and fungi is a genus of entomopathogenic fungi that has garnered increasing attention in recent years due to its diverse ecological roles and promising biomedical applications. This comprehensive review synthesizes the current knowledge surrounding Ophiocordyceps sp., encompassing its taxonomy, life cycle, host specificity, and the intricate mechanisms employed during host colonization. The paper highlights the identification of Ophiocordyceps sp. as well as DNA extraction followed by PCR and sequencing which can help to understands them on how they become a natural regulator of insect populations and its potential as a pesticide for sustainable pest management.